REVITALISASI SEKOLAH BERBASIS TEACHING FACTORY (TEFA) SEBAGAI RUJUKAN SEKOLAH MENENGAH KEJURUAN SWASTA DI PAMEKASAN (STUDI KASUS DI SMKS MAMBAUL ULUM BATA-BATA PANAAN PALENGAAN PAMEKASAN) - Sarifudin, Sarifudin; Suhri, Ahmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Vocational high schools are educational units that are oriented towards preparing students to have skills or expertise in certain fields so that they are ready to enter the world of work and industry both as productive workers and developing themselves to create jobs for themselves and others. The problem formulation of this thesis is the implementation of the Revitalization of Teaching Factory-Based Vocational High Schools (TEFA) as a reference for Private Vocational High Schools in Pamekasan, second, what is the effectiveness of implementing the Revitalization of Teaching Factory-Based Vocational High Schools, third, what is the impact of the Revitalization of Teaching Factory-Based Vocational High Schools? .This research is a descriptive analytical field study with a qualitative approach. Data collection techniques use interviews, participant observation and documentation. Data analysis consists of data reduction, data presentation and drawing conclusions. Checking the validity of the data is carried out through credibility, triangulation and member checks.The results of this research conclude that first: The implementation of teaching factory-based revitalization at Mambaul Ulum Bata-Bata Vocational School is known to have been carried out well, influenced by elements of students, teachers, management and industrial cooperation. Second, aspects of the learning system, teaching staff, students and facilities are effective with products in the form of several drinks, snacks and food whose main ingredients are taken from local farmers. Third, the impact on students, teachers, institutions and the surrounding community becomes relevant in accordance with the Ministry of Education and Culture's instructions through industry-based revitalization activities carried out in schools Sekolah menengah kejuruan adalah satuan pendidikan yang berorientasi untuk menyiapkan peserta didiknya memiliki keterampilan atau keahlian dibidang tertentu sehingga siap memasuki dunia kerja dan industri baik sebagai tenaga kerja yang produktif maupun pengembangan dirinya untuk menciptakan lapangan kerja bagi dirinya sendiri dan orang lain. Rumusan masalah daripada tesis ini adalah implementasi Revitalisasi Sekolah Menengah Kejuruan Berbasis Teaching Factory (TEFA) Sebagai Rujukan Sekolah Menengah Kejuruan Swasta di Pamekasan, kedua, Bagaimana Efektifitas pelaksaaan Revitalisasi Sekolah Menengah Kejuruan Berbasis Teaching Factory, ketiga, Bagaimana Dampak Revitalisasi Sekolah Menengah Kejuruan Berbasis Teaching Factory. Penelitian ini merupakan studi lapangan bersifat deskriptif analisis dengan pendekatan kualitatif. Teknik pengumpulan data menggunakan wawancara, observasi partisipan dan dokumentasi. Analisis data terdiri dari reduksi data, penyajian data dan penarikan kesimpulan. Pengecekan keabsahan data dilakukan melalui kredibilitas, tringulasi dan member ceck. Hasil dari penelitian ini menyimpulkan bahwa pertama: Implementasi revitalisasi berbasis teaching factory di SMKS Mambaul Ulum Bata-Bata dketahui sudah terlaksana dengan baik dengan dipengaruhi oleh unsur siswa, guru, manajemen dan kerja sama industri. Kedua, aspek sistem pembelajaran, tenaga pendidik, peserta didik dan sarana sudah efektif dengan hasil produk berupa beberapa minuman, snack dan makanan yang bahan utamanya mengambil dari petani sekitar. Ketiga, dampak terhadap siswa, guru, lembaga dan masyarakat sekitar menjadi relevan sudah sesuai intruksi Kemendikbudristek melalui kegiatan revitalisasi berbasis industri yang dijalankan di sekolah.